Artroskopická exstirpace osteoidního osteomu hlavice femuru - Zeman, Petr; Skala, Petr; Pilný, Jaroslav (Acta chirurgiae orthopaedicae et traumatologiae Čechoslovaca, 2022)
Osteoid osteoma is a primary benign bone tumor with rare intra-articular occurrence. Our case report describes a rare case of a 21-year-old man with long-term severe pain in the right hip region caused by osteoid osteoma managed by arthroscopic excision. The clinical finding of pains and a limited range of motion did not correlate with the normal plain X-ray finding. The osteoid osteoma was suspected based on the CT scan. In literature, several methods of resection of intraarticular osteoid osteoma of the hip are described. Since our department has long specialised in arthroscopic hip surgery and based on the available examinations the tumor appeared to be located within the arthroscopic reach, we decided for arthroscopic resection of the tumor. Our study comprises a detailed description of the entire surgical procedure, the used arthroscopic approaches and the arthroscopic technique of tumor excision. The histological examination of samples taken from the mass confirmed the suspected osteoid osteoma. The success of arthroscopic excision of the tumor was later confirmed also by very positive postoperative recovery when the patient very soon experienced a considerable reduction of pain observed during our five-year follow-up of the patient (Day 13, Week 2 and 6, Year 1, 2 and 5). During the follow-up period, an increase of the Harris Hip Score (13.5 preoperatively vs 76.6/91/94/96/96 postoperatively) and a decrease in VAS (9 preoperatively vs. 3/1/1/1/1) were reported. The follow-up CT and MRI performed at 2 or 5 years after surgery did not show tumor recurrence. The case report includes also illustrations consisting of X-rays, CT and MRI scans before and after surgery as well as multiple scans taken intraoperatively. It has to be emphasized that this is a rare case and an evaluation of a larger group of patients would be necessary to verify the successful outcomes of arthroscopic technique in treatment of the hip joint osteoid osteoma.
Keywords: Osteoma, Osteoid; bolest; Femur Head; Pain; Young Adult; Bone Neoplasms; mladý dospělý; dospělí; hlavice femuru; Adult; lokální recidiva nádoru; Humans; mužské pohlaví; Male; lidé; nádory kostí; Neoplasm Recurrence, Local; osteom osteoidní